An evaluation of the accuracy of the American College of Sports Medicine metabolic equation for estimating the oxygen cost of running - Ruiz, A.; Sherman, N. W. (The Journal of Strength and Conditioning Research, 1999)
The purpose of this study was to examine the accuracy of the American College of Sports Medicine (ACSM) metabolic equation: o2 (ml·kg1·min 1) = [0.2 × speed (m·min1)] + [1.8 × (% grade)] + 3.5. In this study, 16 men and 17 women performed a 6-minute steady-state run. Steady-state characteristics (mean ± SD) for the men and women running at randomly assigned speeds and grades were as follows: o2submax = 39.2 ± 4.7 ml·kg1·min1 and 31.1 ± 8.1 ml·kg1·min1 and %o2peak = 89.2 ± 8.2% and 79.3± 14.6%, respectively. Results of a dependent t-test revealed the ACSM running equation significantly (t(32) = 5.434; p = 0.0001) overestimated o2submax. The equation overestimated the oxygen cost of running in 29 (88%) of the 33 subjects. In conclusion, the ACSM metabolic equation significantly overestimated the oxygen cost of running in this study.